2008
DOI: 10.1097/pas.0b013e3181804302
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Carcinoma of the Lung

Abstract: Pleomorphic carcinoma (PC) of the lung is rare, and it is classified as a subtype of sarcomatoid carcinoma of the lung in the World Health Organization histologic classification of lung tumors. In this study, 70 cases of PC surgically resected were reviewed to identify its clinicopathologic characteristics. There were 57 men and 13 women, and their mean age was 66 years (range: 29 to 80 y). Sixty-eight tumors contained identifiable epithelial components, and the other 2 consisted of spindle cells and giant cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(76 citation statements)
references
References 29 publications
1
71
0
4
Order By: Relevance
“…According to several published reports of relatively large patient samples, the five‐year OS rate of patients with PC of the lung after surgery is < 40% 6, 11, 12. Yuki et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to several published reports of relatively large patient samples, the five‐year OS rate of patients with PC of the lung after surgery is < 40% 6, 11, 12. Yuki et al .…”
Section: Discussionmentioning
confidence: 99%
“…, 13 Mochizuki et al . reviewed 70 cases of surgically resected PC of the lung and reported that histologically proven massive coagulation necrosis was a poor prognostic factor 6. Fujisaki et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPC is defined as a poorly differentiated non‐small cell lung cancer (NSCLC) containing spindle cells and/or giant cells, or a carcinoma that comprises spindle or giant cells alone, in at least 10% of the tumor 4. It has an aggressive clinical course and can show resistance to chemotherapy, which is an actively applied treatment for NSCLC 5, 6.…”
Section: Discussionmentioning
confidence: 99%